2021
DOI: 10.1177/00938548211008488
|View full text |Cite
|
Sign up to set email alerts
|

Community Service Outcomes in Justice-Involved Youth: Comparing Restorative Community Service to Standard Community Service

Abstract: Traditional mandated community service (CS) typically consists of picking up trash or performing manual labor, distanced from the community. Some juvenile justice programs have begun to implement restorative community service (RCS) programs that enable youth to complete meaningful CS projects in a shame-free manner alongside community members. This study compared RCS with a standard community service (SCS) program in two counties in Washington State on psychosocial outcomes, including attitudes, peer relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In general, it involves the juvenile carrying out simple tasks, for example, picking up garbage. 24 Currently, it is increasingly indicated that this does not yield adequate educational effects. Beginning in 2001, the Clark County Juvenile Court in Washington State, US, has begun U M C S using restorative community service (RCS) instead of standard community service (SCS) against juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…In general, it involves the juvenile carrying out simple tasks, for example, picking up garbage. 24 Currently, it is increasingly indicated that this does not yield adequate educational effects. Beginning in 2001, the Clark County Juvenile Court in Washington State, US, has begun U M C S using restorative community service (RCS) instead of standard community service (SCS) against juveniles.…”
Section: Discussionmentioning
confidence: 99%